The Impact of Digital Leadership in Strategic Foresight / An Applied Research in Al-Rafidain Bank - Jawad Jassim , Kadhim; Al-Kubaisy, Salah Al-Deen (Journal of Economics and Administrative Sciences, 2024)
The business environment today is characterized by many changes, especially in the technological field. So, organizations require to keep pace with these changes by adopting new methods in providing products and services, including the adoption of digital leadership that is able to anticipate the future to seize opportunities in exploiting current resources while introducing new resources to achieve professional development in the all levels of the organization, which contributes to provide the best services and products to clients to gain their satisfaction and loyalty. The research problem is represented by asking a main question, which is (How can the administrative leaders of Al-Rafidain Bank employ digital leadership mechanisms to develop strategic foresight capabilities?), due to a variety of factors, such as misemployment of technology brought on by managers’ lack of digital skills in providing banking services, which requires the adoption of digital leadership that contributes to the transition from traditional management to modern management that works to provide the best services that competitors cannot provide it, which leads to enhance the sustainability of the organization. The goal of this research is to investigate how the Al-Rafidain Bank’s computerized initiative contributes to strategic foresight. The research sample was represented by the heads of departments and branches from Baghdad and the governorates, totaling (133) managers. The results demonstrated a substantial influence of digital leadership in boosting strategic foresight by applying proper statistical tools, such as the arithmetic mean, standard deviation, coefficient of variation, and the statistical program (SPSS) and (AMOS). Research type: Research Paper